Puariti Font: Visual Literacy and Ideology in the Cultural Identity of Iban Tribe, Malaysia - Nadia Sigi Prameswari; Agus Cahyono; Slamet Subiyantoro; Eko Haryanto (Future Science, 2023)
This study aims to identify the meaning embedded in the Puariti font and explore the visual literacy and ideological content in the Puariti font and its relevance in social practice. This study is a textual analysis using a cultural study approach especially on ideological theory in examining the Puariti font due to the solid cultural characteristics of the font and its long process of cultural transformation. According to the results, the Puariti font represents Pua Kumbu in the form of metamorphic letters. This font is composed of Engkaramba and anthropomorphic motifs belonging to the upper-class motifs of the Iban society. Further, Puariti can serve as a symbol of Iban culture amid globalization. This font embeds an essential meaning that connects the Iban people with the eternal meaning of their life and cosmology, history, and their relationship to the physical environment. That, taking part in maintaining the boundaries and construction of the Iban identity can help distinguish the Ibans from others. The cultural identity and expression of Iban religiosity are represented through Puariti font. Despite changing from the sacred Pua Kumbu cloth to the digital version of the Puariti font, the condition shows the same physical and metaphysical reality as the embodiment of reality and an ideology. The existence of the Puari-ti font can function as a visual literacy medium in art education inheritance practice, assisting the younger generation as agents of cultural production to revive traditional and cultural values.